Literature Review on Pre-Service Teachers' Understanding of Social Studies Learning in Elementary Schools - Wildan Nuril Ahmad Fauzi; Deni Puji Hartono; Yuli Setiawati; Agnes Amila Wigati (MANDALIKA : Journal of Social Science, 2024)
This study aims to identify and understand pre-service teacher candidates' understanding of the concept of social studies learning in elementary schools and find effective strategies to improve teacher creativity in the learning process. This study used a qualitative method with a literature study approach, collecting data from various sources such as articles, books, and other related research. The main findings show that a strong professional identity, continuous professional development, and supportive education policies are essential to improve the quality of social studies teaching. In addition, innovative teaching strategies such as gamification have proven effective in increasing student motivation and engagement. Diversification and inclusion in social studies teacher education and training were also identified as important factors. This research is expected to contribute significantly to improving the quality of basic education in Indonesia through more effective training and professional development programs for prospective teachers